2018
DOI: 10.3389/fncel.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Activity of TRPM4 in Medial Prefrontal Cortex Layer 2/3

Abstract: TRPM4 is a Ca2+-activated non-selective cationic channel that conducts monovalent cations. TRPM4 has been proposed to contribute to burst firing and sustained activity in several brain regions, however, the cellular and subcellular pattern of TRPM4 expression in medial prefrontal cortex (mPFC) during postnatal development has not been elucidated. Here, we use multiplex immunofluorescence labeling of brain sections to characterize the postnatal developmental expression of TRPM4 in the mouse mPFC. We also perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…In excitable cells, it is regarded as the most suitable signaling mechanism to boost the depolarizing drive following an increase in electrical activity, which reflects into the activation of voltage-gated Ca 2+ channels (Petersen, 2002). Emerging evidence showed that TRPM4 is actually recruited by an increase in cytosolic Ca 2+ concentration to generate a DISC current and finely tune neuronal excitability in several brain areas (Lei et al, 2014;Menigoz et al, 2016;Riquelme et al, 2018). For instance, TRPM4 mediates the depolarizing afterpotential and phasic bursting observed in supraoptic and periventricular nuclei of the hypothalamus after a train of action potentials (Teruyama et al, 2011) and contributes to increase the firing rate in PCs (Kim et al, 2013).…”
Section: Trpm4 Channels In Granule Cellsmentioning
confidence: 99%
“…In excitable cells, it is regarded as the most suitable signaling mechanism to boost the depolarizing drive following an increase in electrical activity, which reflects into the activation of voltage-gated Ca 2+ channels (Petersen, 2002). Emerging evidence showed that TRPM4 is actually recruited by an increase in cytosolic Ca 2+ concentration to generate a DISC current and finely tune neuronal excitability in several brain areas (Lei et al, 2014;Menigoz et al, 2016;Riquelme et al, 2018). For instance, TRPM4 mediates the depolarizing afterpotential and phasic bursting observed in supraoptic and periventricular nuclei of the hypothalamus after a train of action potentials (Teruyama et al, 2011) and contributes to increase the firing rate in PCs (Kim et al, 2013).…”
Section: Trpm4 Channels In Granule Cellsmentioning
confidence: 99%
“…A key aspect of PD pathophysiology is neuroinflammation in the SNpc, where reactive astrocytes and microglia intersect the key cellular functions affected in PD, namely, oxidative stress and the inflammatory response, endoplasmic reticulum (ER) stress, mitochondrial, lysosomal, proteosomal and autophagic functions, converging to α-Syn aggregation and prion-like cell-to-cell transmission of α-Syn [ 25 , 74 , 75 , 76 , 77 ].…”
Section: A Dual Role For Glia In Parkinson’s Diseasementioning
confidence: 99%
“…Despite that, TRPM4 regulates Ca 2+ signals in different cell types, such as fibroblasts (Cáceres et al, 2015), mastocytes (Shimizu et al, 2009), dendritic cells (Barbet et al, 2008), and lymphocytes (Launay et al, 2004). TRPM4 expression has been described in hypothalamus (Teruyama et al, 2011), hippocampal CA1 area (Menigoz et al, 2016), preBötzinger nucleus (Picardo et al, 2019), and medial prefrontal cortex (Riquelme et al, 2018). Interestingly, TRPM4 increases Rac1 activity in MEF cells (Cáceres et al, 2015).…”
Section: Trpm4mentioning
confidence: 99%
“…These features and the wide expression of these channels in multiple tissues and cell types, grant a high level of complexity to their role in diverse physiological and pathophysiological processes ( Venkatachalam and Montell, 2007 ). In this context, several TRP channels are implicated in cellular processes related to central nervous system (CNS) functioning such as the modulation of neuronal excitability ( Mickle et al, 2016 ; Hong et al, 2020b ), maturation or establishment of subcellular structures such as dendrites ( Tai et al, 2008 ), excitatory synapses ( Zhou et al, 2008 ), axonal outgrowth ( Jang et al, 2014 ), frontal cortex postnatal development ( Riquelme et al, 2018 ) and brain blood flow regulation ( Earley et al, 2004 ; Cornillot et al, 2019 ). Also, current evidence suggests that TRP channels could regulate downstream processes such as gene expression or more lasting effects, like Long Term Potentiation (LTP).…”
Section: Trp Channelsmentioning
confidence: 99%